On-axis structured beams generation via moiré and Mie resonant metallo-dielectric moiré gratings - Anil Ringne; Subrata Karmakar; Ananth Krishnan (Scientific Reports)
Abstract Structured beams carrying orbital angular momentum have been generated conventionally using spiral phase plates, fork gratings, and metasurfaces. Spiral phase plates are non-planar, fork gratings do not produce structured beams on the axis, and metasurfaces need subwavelength unit cell level design. In this work, we show a method to generate on-axis structured beams, at the zeroth order of a diffraction grating with experimentally relevant efficiency using moiré patterned binary gratings that are compatible with planar fabrication, do not need subwavelength unit cell level design, and can be used with a spatial light modulator. By logically superposing two binary forked gratings, we create a moiré pattern that enables on-axis structured beam generation at the zeroth order of the diffraction grating. We demonstrate, using experiments and simulations, the generation of on-axis zeroth order structured beams using spatial light modulator based reconfigurable moiré gratings and Mie resonant metallo-dielectric standalone moiré gratings, showcasing the versatility of this approach in different configurations. Simulations and experiments demonstrate that the on-axis structured beam is generated by the moiré pattern within the gratings, and its shape is determined by the topological charges of the overlapping binary forked gratings. Additionally, we demonstrate color-selective on-axis structured beam generation at the zeroth order of the grating, where the color-selectivity of the on-axis structured beam depends on the grating period and arises due to Mie resonance in standalone nanofabricated metallo-dielectric moiré gratings. The on-axis structured beam generation at the zeroth order of the grating using the proposed method may have several applications, including sensing and optical trapping.